Understanding the Roots and Impacts of Conflict on School Culture and Behavior - Albon, Lorraine; Cruz, Yvonne (Journal of Interdisciplinary Perspectives, 2025)
This study explored the causes and consequences of conflict and their effects on school culture behaviors within the Division of Siquijor. Several studies reviewed were more focused on the personal effects of conflict and the lack of knowledge as to the impact of conflict on the school culture behavior is the primary evidence of knowledge gap, hence, this study was conducted. A. total of 125 respondents participated in the research, which utilized a descriptive-correlational design for data collection and analysis. Data were gathered through a structured survey questionnaire, and statistical treatments included mean calculations, multiple linear regression, the Mann-Whitney U-test, the Kruskal-Wallis H-test, and the DSCF Test. Key findings revealed that teachers experience conflict to a "Moderate" extent and perceive both the negative and positive consequences of conflict at a "High Degree." Additionally, the school culture behaviors were rated as "Very High." While no significant relationship was found between the extent of conflict faced by teachers and its positive consequences, a correlation was observed concerning the negative consequences. Furthermore, no significant relationship existed between the level of conflict experienced and the overall school culture behavior. Notably, the number of teachers within a school was identified as a factor influencing variations in school culture behavior. This research highlights the intricate nature of conflict within educational environments and its subtle effects on school culture, offering valuable perspectives for future intervention strategies and policy formulation.